2021
DOI: 10.3389/fimmu.2021.645124
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Interferon-γ Restores Monocytic Human Leukocyte Antigen Receptor (mHLA-DR) in Severe COVID-19 With Acquired Immunosuppression Syndrome

Abstract: BackgroundThe major histocompatibility complex (MHC) class II characterized by monocytes CD14+ expression of human leukocyte antigen receptors (HLA-DR), is essential for the synapse between innate and adaptive immune response in infectious disease. Its reduced expression is associated with a high risk of secondary infections in septic patients and can be safely corrected by Interferon-y (IFNy) injection. Coronavirus disease (COVID-19) induces an alteration of Interferon (IFN) genes expression potentially respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Immune stimulation by IFNγ in our case was similar to that reported previously in another infectious context and appears to be efficient in severe COVID-19 ( 9 11 ). AIS has been described in COVID-19 patients in the ICU, but few data on immunostimulation have been reported to date.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Immune stimulation by IFNγ in our case was similar to that reported previously in another infectious context and appears to be efficient in severe COVID-19 ( 9 11 ). AIS has been described in COVID-19 patients in the ICU, but few data on immunostimulation have been reported to date.…”
Section: Discussionsupporting
confidence: 90%
“…The resistance profiles of the detected invasive bacterial species Klebsiella pneumoniae (three different pulsed-field gel electrophoresis (PFGE) types), Pseudomonas aeruginosa , Acinetobacter baumannii , and Citrobacter freundii left very limited antimicrobial options, warranting an investigation of the potential for immunomodulation by IFNγ. The observed AIS with low expression of HLA-DR in circulating monocytes prompted us to apply IFNγ therapy as in previously described cases ( 9 11 ). This resulted in a significant increase in mHLA-DR levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…With the increasing understanding of COVID-19 associated immune dysregulation, immune modulation therapy appears to be the next step forward. Dickel S et al reported a single case of superinfected COVID-19 patient with ARDS treated with a single dose of interferon-gamma (IFN-Y) with measurement of mHLA-DR pre and post-therapy; a sharp increase in mHLA-DR was reported [ 36 ]. Another case of immunostimulation with IFN-Y in protracted SARS-Cov-2 pneumonia resulted in recovery and discharge in a patient with several comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Updated RUCAM is a standardized and validated method specific to hepatotoxicity and has long been well-established in hepatological practice, studies, registries, and case reports ( Benichou et al, 1993 ; Danan and Benichou, 1993 ). The expression of HLA-DR on CD14 + monocytes and CD3 + T lymphocytes was analyzed using flow cytometry, as previously described ( Dickel et al, 2021 ; Grimm et al, 2021 ; Baier et al, 2022 ; Tampe et al, 2022 ). Antibody staining followed standard protocols for antibody staining of cells in suspension.…”
Section: Methodsmentioning
confidence: 99%